1992
DOI: 10.1159/000261465
|View full text |Cite
|
Sign up to set email alerts
|

Enamel and Plaque Fluoride following Glass Ionomer Application in vivo

Abstract: Glass ionomer fillings have been suggested to act as a fluoride-releasing system in the mouth. The aim of the present study was to evaluate whether a glass ionomer slab applied on the enamel can increase the fluoride content of the enamel and plaque of adjacent teeth in real-life conditions with frequent exposure to fluoride from other sources. Twenty-five adults living in a town with fluoridated drinking water participated in the study. The initial enamel fluoride content on the buccal surface of the contrala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…Furthermore, all samples were placed below the acrylic margin level of the intra-oral devices to allow plaque accumulation and to simulate what would happen in a child with an erupting tooth that is not adequately cleaned. Consequently, as mentioned by some authors 21,26,28 , the fluoride accumulated in the dental plaque (biofilm) and the decreased number of S. mutans and Lactobacillus gave rise to the remineralization of the artificial caries lesions. Some investigations have demonstrated and proven that along the GIC restorations there is a certain amount of bacterial inhibition 21,25,28 .…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, all samples were placed below the acrylic margin level of the intra-oral devices to allow plaque accumulation and to simulate what would happen in a child with an erupting tooth that is not adequately cleaned. Consequently, as mentioned by some authors 21,26,28 , the fluoride accumulated in the dental plaque (biofilm) and the decreased number of S. mutans and Lactobacillus gave rise to the remineralization of the artificial caries lesions. Some investigations have demonstrated and proven that along the GIC restorations there is a certain amount of bacterial inhibition 21,25,28 .…”
Section: Discussionmentioning
confidence: 96%
“…Seppä, et al . demonstrated that GICs may affect acid production and electrolyte metabolism of S. mutans (27). Fluoride release from these material combined with a pH fall around the material seems to be the most probable reason of the perturbation of Streptococcus metabolism (6).…”
Section: Discussionmentioning
confidence: 99%
“…In several stud ies, the fluoride concentration of plaque growing on, or ad jacent to, glass ionomer has been found to be increased [Forss et al, 1991;Hallgrcn ct al., 1993;Benelli et al, 1993], but no increase was found in the study of Seppa et al [1992], study o f Berg et al [1990], the effect was only temporary, and in the study of van Dijken et al [1991], no reduction of mutans streptococci or lactobacilli was found in plaque on 1-year-old glass ionomers.…”
mentioning
confidence: 99%